The Social Enterprise Craze: CSO Financial Sustainability in Ghana - Oeding Noemí; Newby Kara (Nonprofit Policy Forum)
As a relatively stable democracy, Ghana has long been a popular country for international donors. However, recent changes in its classification by the World Bank and government proclamations have led to a reduction in foreign aid, forcing Civil Society Organizations (CSOs) to confront the financial sustainability of their organizations. In this study, we test the typology proposed by Arhin et al. (2018. “Facing the Bullet? Non-Governmental Organisations’ (NGOs’) Responses to the Changing Aid Landscape in Ghana.” Voluntas: International Journal of Voluntary and Nonprofit Organizations 29 (2): 348–60) which finds that CSOs in Ghana are using six different strategies to work toward financial sustainability. Based on an original survey of 42 CSOs, our findings indicate an almost exclusive focus on income generation in the form of social enterprises. The challenges this poses to the sector are discussed.